Testing the larvacides activities of clove leaves extract (Syzygium aromaticum) on the mortality of Aedes Aegypti L. - Ariyani Buang; Farid Fani Temarwut; Suprapto Prayitno (Universitas Aisyah Pringsewu, 2023)
Dengue Hemorrhagic Fever (DHF) is an infection caused by the dengue virus which is transmitted by the Aedes Aegypti mosquito. Clove leaves (Syzigum aromaticum) is a part of a plant that contains eugenol, saponins, flavonoids and tannins which are useful as natural larvicides against Aedes Aegypti mosquito larvae.This study aims to determine the effect of larvicides Clove leaf extract (Syzigium aromaticum) on Aedes aegypti L larvae and to determine the LC50 value that can kill Aedes aegypti L larvae. This study was an experimental study with a post test only group control design. Clove leaves were extracted by maceration using 96% w/v ethanol.This study was divided into 7 groups using Aedes aegypty Instar III larvae, namely:2 control groups namely K1 NaCMC 1% as negative control and K6 Abate 0.1% b/v as positive controland 5 treatment groups each with a concentration of clove leaf extract K20.010 % w/v, K3 0.025 % w/v, K4 0.05 % b/v, K5 0.075 % b/v and K6 0.100 % b/v.The number of larvae deaths was counted after 24 hours.HThe results of the study showed that the number of deaths of Aedes aegypti mosquito larvae for each group was: K1 0%, K2 3.33%, K3 8.33%, K4 23.33%, K5 53.33%, K6 80% and K7 100 %Analysis results statistics using Anova. and the LSD follow-up test isthere was a significant difference in larval mortality at each concentration (p 0.00 less than 0.05) And K2 showed a non-significant effect with K3 (sig p 0.089 more than 0.05). From the research results it can be concluded that clove leaf extract (Syzygium aromaticum L) has a larvicidal effect on Aedes aegypti larvae. Clove leaf extract (Syzygium aromaticum) can kill Aedes aegypti mosquito larvae with an LC50 value of 600 ppm and is included in the toxic category.